The ANALYSIS OF FACTORS INFLUENCING STUDENTS FOR CHOOSING BACHELOR’S IN ACCOUNTING PROGRAM AT FACULTY OF ECONOMY AND BUSINESS, CHRISTIAN UNIVERSITY OF INDONESIA - Sembiring, Carolina F.; Sidharta, Juaniva; Simanjuntak, Ramot P. (Fundamental Management Journal, 2019)
FEB UKI experienced the problem of fluctuating the number of students who should be addressed by improving the quality of service through improving the quality of human resources in UKI, so that it would have an impact on the interest of prospective new students to choose FEB UKI and ultimately influence their level of satisfaction. Therefore, it is necessary to know what factors influence students choosing to study at the FEB UKI Accounting Undergraduate study program. The results showed that 1) Factors influencing old students choosing yo study in the S-1 Accounting Study Program FEB UKI were factors 1 such as person variables, physical evidence, prosesses, products and costs, while factor 2 such as reference group variables, self and family desires. 2) Factors influencing new students choosing to study at the S-1 Accounting Study Program FEB UKI are factors 1 such as cost variable, own desire, person, promotion, group references, and process, while factor 2 is product variable, physical evidence, and family. Keywords: Factor influencing students for choosing Accounting Undergraduate Program, Factor Analysis, Confirmatory Factor Analysis.